The Effect of Self Efficacy and Learning Independence on English Speaking Ability - Natalia Tri Astuti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2022)
This study aims to determine and analyze the effect of self-efficacy and learning independence on students' speaking skills in English. The research method used is a survey method with correlational analysis conducted on semester one students of the informatics engineering study program for the even academic year 2020/2021. The sampling technique is simple random sampling technique of 70 students. The instruments used are questionnaires and tests. The data was analyzed first by testing the data analysis requirements met, namely normality test, regression linearity test and multicollinearity test. After the test data requirements are met, a differential analysis is carried out to test the research hypotheses using correlation analysis and multiple regression techniques. From the results of the study it was found that: (1) there was a positive and significant effect of self-efficacy and independent learning together on students' English speaking skills; (2) there is a positive and significant effect of self-efficacy on students' English speaking skills; (3) there is a positive and significant effect of learning independence on students' English speaking skills.